Undergraduate Students’ Experiential Motives when Expressing Bajingan as Their Expletive - Didik Rinan Sumekto; Kustinah Kustinah (Humaniora, 2019)
This study attempts at investigating students’ expletive motives revealing at their experiential life. 177 students majoring in English, Javanese, and Indonesian participated in this study. Data were collected from closed and opened questionnaires focusing on self-rated perception of Scherer and Sagarin’s (2006) ten swearing motives and Nicolau and Sukamto’s (2013) male and female attitudes toward expletive. Analyses used the descriptive and non-parametric statistics. Significant differences among four swearing motives were not found. But, the motive of acting cool indicated a significant difference (p=.000). The negative Z value (Z=-1.910) for anger expression, (Z=-.875) for peer pressure, (Z=-1.567) for tensions and frustrations relief, (Z=-3.607) for part of acting cool, and (Z=-.225) for society acceptance. The findings also indicated 10.2% females and .7% males confirmed bajingan as a wagon driver, whereas 70% females and 25% males stated it as an expletive. Males showed a predominant expletive more than females toward male and mixed gender. TV program was determined as the mostly influenced media. This expletive deals with intra-and inter-individual contexts deducing positive or negative reactions.